2022
DOI: 10.1158/2326-6066.cir-22-0157
|View full text |Cite
|
Sign up to set email alerts
|

BCG-Induced Tumor Immunity Requires Tumor-Intrinsic CIITA Independent of MHC-II

Abstract: For decades, BCG immunotherapy has been the standard of care for non–muscle-invasive bladder cancer. Despite this clinical experience, the mechanism by which BCG stimulates tumor-eliminating immunity is unclear, and there is still a need for more accurate prediction of clinical outcomes in advance of treatment initiation. We have shown that BCG stimulates tumor-specific T-cell immunity that requires tumor cell expression of the IFNγ receptor (IFNGR); however, the downstream components of IFNGR signaling respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Despite its well-established clinical efficacy, the detailed mechanisms by which BCG controls tumors have remained elusive. Recent evidence in mouse models and human patients indicated that BCG-mediated tumor rejection is dependent on tumor specific T cells (21)(22)(23). The accepted model of anti-tumor effects of BCG, and the rationale for its administration in the bladder, was that it acts as a local immunotherapy at the site of administration to improve anti-tumor T cell priming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its well-established clinical efficacy, the detailed mechanisms by which BCG controls tumors have remained elusive. Recent evidence in mouse models and human patients indicated that BCG-mediated tumor rejection is dependent on tumor specific T cells (21)(22)(23). The accepted model of anti-tumor effects of BCG, and the rationale for its administration in the bladder, was that it acts as a local immunotherapy at the site of administration to improve anti-tumor T cell priming.…”
Section: Discussionmentioning
confidence: 99%
“…Following bladder instillation, BCG attaches to urothelial cells (13)(14)(15)(16), resulting in recruitment and tumor infiltration of myeloid and lymphoid cells in both humans and mice (17,18). In mouse models, bladder tumor rejection is mediated by tumor specific CD4 and CD8 T cell immunity (19)(20)(21)(22). Complementary evidence from human studies has identified tumor-specific CD4 T cells in BCG-treated patients with NMIBC (23).…”
Section: Introductionmentioning
confidence: 99%